EFFICIENCY OF RADIODIAGNOSIS METHODS IN DETECTING STRUCTURAL CHANGES IN TISSUES ASSOCIATED WITH TRAUMATIC BRAIN INJURY - Magerrambeyli, I.Sh. (World of Medicine and Biology, 2023)
Combined craniocerebral injuries, which occupy one of the first places among peacetime injuries and are the most characteristic of road traffic accidents, can reach 70-92% in terms of prevalence. The aim of the study was to compare the studied clinical diagnostic parameters associated with various forms of traumatic brain injury. To achieve this goal, a prospective comparative study of 299 people with traumatic brain injuries hospitalized in the period from 2016 to 2020 was conducted. and the complex use of clinical and instrumental methods of research in various forms of isolated and combined injuries was performed. Pronounced deviations in the prevalence of traumatic brain injury are detected at the age of up to 20 years and older than 70 years, and where the lowest level of traumatic brain injury was noted, the rate increased, reaching a maximum at the age of 20–29 years and 40–49 years. The results of radiodiagnosis testify to the effectiveness of X-ray when used in patients with various post-traumatic complications (χ2=6.233, df=2, p=0.044).